Model Integrasi Teologi dan Pendidikan: Kajian Komparatif Pemikiran Agustinus dari Hippo, John Amos Comenius, Dan Paulo Freire - Rumiyati Rumiyati (KAPATA: Jurnal Teologi dan Pendidikan Kristen, 2025)
This article examines models of integration between theology and education through a comparative analysis of three major figures: Augustine of Hippo (354–430 CE), John Amos Comenius (1592–1670 CE), and Paulo Freire (1921–1997 CE). Employing a qualitative research method based on library research and content analysis, this study identifies three distinct yet complementary integration models: the hierarchical-theocentric model (Augustine), the pansophic-encyclopedic model (Comenius), and the praxis-dialogical model (Freire). The analysis reveals that the development of theology-education integration models moves from a spiritualist-individual orientation toward a social-transformative orientation without losing its theological essence. A synthesis of these three models yields an integrative framework relevant to contemporary Christian education in Indonesia, encompassing epistemological, anthropological, and praxiological dimensions.